The Accessible Museum: Towards an Understanding of International Audio Description Practices in Museums. (November 2020) - Hutchinson, Rachel S.; Eardley, Alison F.
Introduction: Audio description (AD) in museums is crucial for making them accessible for people with visual impairments. Nevertheless, there are limited museum-specific AD guidelines currently available. This research examines current varied international practitioner perspectives on museum AD, focusing on imagery, meaning, emotion and degrees of objectivity, and the regional differences (Europe and United States) in AD traditions, in order to better understand how AD can be used to enhance access to museums. Methods: Forty-two museum describers from 12 countries responded to a questionnaire requiring fixed-choice and free-text responses about the purpose and construction of museum AD. Results: Inference tests showed that European describers agreed more strongly than American describers that AD should "explore meaning" ( U = 91.00, N 1 = 24, N 2 = 14, p = .03), and "create an emotional experience" ( U = 89.50, N 1 = 24, N 2 = 14, p = .03), rating the use of cognitive prompts as more important ( U = 85.50, N 1 = 21, N 2 = 14, p = .04). Qualitative data enriched this understanding by exploring participant responses on the themes of mental imagery, objectivity and interpretation and cognitive prompts. This highlighted broader agreement between regions on mental imagery, but more acceptance of interpretation in AD from the European respondents. Discussion: American and European describers' opinions differ regarding the purpose of AD: whether it is about conveying visual information or whether broader interpretations should be incorporated into descriptions for audiences with visual impairments. Implications for practitioners: These findings indicate that further discussion is needed regarding the purpose of museum AD and, in particular, the way in which objectivity is contextualized. They raise questions about AD providing visual information and/or seeking to address a wider museum experience, including the stimulation of curiosity or emotion.